Alternatives to Spontaneous Speech Elicited Translation and Imitation as Indicators of Second Language Competence. Working Papers on Bilingualism, No. 3 - Swain, Merrill; Ontario Inst. for Studies in Education, Toronto. Bilingual Education Project ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Elicited imitation occurs in an experimental situation during which subjects are requested to repeat a model sentence constructed so as to include specific desired grammatical structures. Elicited translation involves giving subjects a sentence in one language, and asking them to say the same thing, but in another language; elicited translation may work from native language to second language or vice versa. This study finds both methods useful as indicators of second language competence. Imitation taps both comprehension and production; data obtained through imitation may be interpreted to determine the stage of acquisition of a given structure. Translation also taps aspects of second language competence, although additional investigation is needed into the translation process itself and into other variations of the translation task. (Author/DB)
ERIC Note: For related documents, see FL 006 676, FL 006 677, FL 006 679.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communicative Competence (Languages); Comprehension; Data Collection; Imitation; Intellectual Development; Language Acquisition; Language Proficiency; Language Research; Linguistic Competence; Linguistic Performance; Research Methodology; Second Language Learning; Translation; Reports, Research